2017
DOI: 10.4172/2380-2391.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Additives in Cotton Bleaching Efficiency

Abstract: Bleaching efficiency is evaluated by the degree of whiteness, absorbency, copper number, tendering factor, strength or strength loss, dye uptake, alkali solubility, degree of polymerization and chemical transformation. Recent lab-scale studies have proven ozone to bleach with efficiency comparable to the conventional bleaching agents and hydrogen peroxide at faster rates without requiring heating or any other supportive treatment with less energy and water. Ozone alone, however, showed poor efficiency in pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It was determined in this study that Ozone bleaching process containing additives provided a better whiteness degree and water absorbency than those obtained ozone alone process to cotton fabrics. [19] In a study, combination of ozone and ultrasound method was applied together to remove the sizing. This study shown that the results of desizing efficiency was nearly similar with those of conventional process [20].…”
Section: Introductionmentioning
confidence: 99%
“…It was determined in this study that Ozone bleaching process containing additives provided a better whiteness degree and water absorbency than those obtained ozone alone process to cotton fabrics. [19] In a study, combination of ozone and ultrasound method was applied together to remove the sizing. This study shown that the results of desizing efficiency was nearly similar with those of conventional process [20].…”
Section: Introductionmentioning
confidence: 99%